Shrimp TAB1 interacts with TAK1 and p38 and activates the host innate immune response to bacterial infection. (August 2017) - Wang, Sheng; Li, Mengqiao; Yin, Bin; Li, Haoyang; Xiao, Bang; Lǚ, Kai; Huang, Zhijian; Li, Sedong; He, Jianguo; Li, Chaozheng
Highlights: The first TAB1 protein (LvTAB1) is identified from pacific white shrimp Litopenaeus vannamei . The first experimental evidence shows LvTAB1 interacts with both LvTAK1 and Lvp38. LvTAB1 is involved in regulating the activation of antimicrobial peptide genes. LvTAB1 plays a protective role in Vibrio parahaemolyticus infection. Abstract: Mammalian TAB1 has been previously identified as transforming growth factor-β (TGF-β)-activated kinase 1 (TAK1) binding protein, which functions as the activator of TAK1 and p38. This report, for the first time, identified and characterized the homolog of TAB1 in shrimp, to be specific, the homolog gene from Litopenaeus vannamei, containing a 1560-bp open reading frame (ORF) that encoded a putative protein of 519 amino acids with the conserved PP2Cc (Serine/threonine phosphatases, family 2C, catalytic) domain in N-terminal and a TAK1 binding motif in C-terminus, has been cloned and named LvTAB1. LvTAB1 was most abundant in gills and its expression could respond significantly to a series of stimuli, including LPS, Vibrio parahemolyticus and Staphylococcus aureus . Moreover, Co-immunoprecipitation (Co-IP) experiments showed that LvTAB1 could combine with LvTAK1 as well as Lvp38, two members of IMD-NF-κB/MAPK pathway, which meant LvTAB1 could have a role in regulating the activities of these kinases. Over-expression of LvTAB1 in drosophila S2 cells could improve the transcriptional levels of antimicrobial peptide genes (AMPs) such as Diptericin (Dpt), the hallmark of drosophila NF-κB activated genes, indicating its activation effect on NF-κB pathway. Furthermore, suppression of LvTAB1 expression in vivo by RNA-interference increased the sensibility of shrimps to V. parahaemolyticus infection, implying its protective role against bacterial infection. In conclusion, these results provide some insight into the function of LvTAB1 during bacterial infection.